The Legacy of the Waqf Institution in Kosovo during the Period of Sultan Abdulhamid II - Avdija, Fahri (Jordan Journal for History and Archaeology, 2024)
This article explores the history of the establishment of Ottoman waqf institutions in Kosovo, with specific emphasis on the reign of Sultan Abdulhamid II. Through the analysis of primary sources from the Ottoman Archive in Istanbul and the General Directorate of Foundations Archive in Ankara, the study provides a comprehensive overview of the awqaf established by Sultan Abdulhamid II himself, statesmen and the common people known as reaya. The research found that while the first waqf institutions in Kosovo were established by sultans and were large complexes known as külliye, later in the late nineteenth and early twentieth centuries, they were established more by the people of the region and were usually small places of worship and other waqf institutions that provided material income such as shops and monetary foundations. The implications of these findings shed light on the role of waqf in the development of Kosovo’s social and economic structures during the late Ottoman period.